2018
DOI: 10.3390/w10040512
|View full text |Cite
|
Sign up to set email alerts
|

Bioturbation Effects of Chironomid Larvae on Nitrogen Release and Ammonia-Oxidizing Bacteria Abundance in Sediments

Abstract: Abstract:The purpose of this work was to reveal the Chironomid larvae bioturbation impact on N release and to find the mechanism of bioturbation to N conversion at the SWI (sediment-water interface). Sampling at four points during a 35-day incubation experiment was conducted. Two in situ techniques (microelectrode and Peeper) were used to capture more realistic and accurate microenvironment information around U-shaped corridors. The results demonstrate that the concentrations of ammonia nitrogen (NH 4 + ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Small chironomid species such as Chironomus riparius construct burrows in the upper 1 cm layer where they directly (grazing) or indirectly (burrow ventilation) affect nitrification processes [15]. Larger species, such as C. plumosus or Chironomus sp., can construct burrows down to 10 cm, significantly extending the niche for nitrifiers and consequently enhancing N-cycling rates [21,54]. Therefore, our findings cannot be generalized for all chironomid species or other macrobenthic invertebrates.…”
Section: Discussionmentioning
confidence: 88%
“…Small chironomid species such as Chironomus riparius construct burrows in the upper 1 cm layer where they directly (grazing) or indirectly (burrow ventilation) affect nitrification processes [15]. Larger species, such as C. plumosus or Chironomus sp., can construct burrows down to 10 cm, significantly extending the niche for nitrifiers and consequently enhancing N-cycling rates [21,54]. Therefore, our findings cannot be generalized for all chironomid species or other macrobenthic invertebrates.…”
Section: Discussionmentioning
confidence: 88%
“…(2021) found the mean FnormalNnormalO3 ${F}_{\mathrm{N}{{\mathrm{O}}_{3}}^{-}}$ in bioturbation system induced by chironomids was 3.19 times that of the control without chironomids. Other field observations have also shown that bioturbation significantly enhances NO 3 − transport and denitrification reactions (Mermillod‐Blondin et al., 2003, 2004; Politi et al., 2021; Stief & de Beer, 2006; Xing et al., 2018; Yang et al., 2021).…”
Section: Resultsmentioning
confidence: 93%